Tobacco NUP1 transports both tobacco alkaloids and vitamin B6. (May 2015) - Kato, Keita; Shitan, Nobukazu; Shoji, Tsubasa; Hashimoto, Takashi
Graphical abstract: The tobacco purine permease-family transporter, nicotine uptake permease 1 (NtNUP1), is shown here to import not only tobacco alkaloids but also vitamin B6, demonstrating relaxed substrate preference to compounds containing a pyridine ring. Highlights: Tobacco nicotine uptake permease (NUP1) is a plasma membrane-localized transporter. NUP1 belongs to the same subclade as Arabidopsis PUP1, which transports vitamin B6. NUP1 was expressed in budding yeast and in cultured tobacco cells. NUP1 was shown to mediate efficient uptake of both tobacco alkaloids and vitamin B6. Abstract: The purine permeases (PUPs) constitute a large plasma membrane-localized transporter family in plants that mediates the proton-coupled uptake of nucleotide bases and their derivatives, such as adenine, cytokinins, and caffeine. A Nicotiana tabacum (tobacco) PUP-family transporter, nicotine uptake permease 1 (NtNUP1), was previously shown to transport tobacco alkaloids and to affect both nicotine biosynthesis and root growth in tobacco plants. Since Arabidopsis PUP1, which belongs to the same subclade as NtNUP1, was recently reported to transport pyridoxine and its derivatives (vitamin B6), it was of interest to examine whether NtNUP1 could also transport these substrates. Direct uptake measurements in the yeast Saccharomyces cerevisiae demonstrated that NtNUP1 efficiently promoted the uptake of pyridoxamine, pyridoxine, anatabine, and nicotine. The naturally occurring ( S )-isomer of nicotine was preferentially transported over the ( R )-isomer. Transport studies using tobacco BY-2 cell lines overexpressing NtNUP1 or PUP1 showed that NtNUP1, similar to PUP1, transported various compounds containing a pyridine ring, but that the two transporters had distinct substrate preferences. Therefore, the previously reported effects of NtNUP1 on tobacco physiology might involve bioactive metabolites other than tobacco alkaloids.